THE ATTEMPT OF IMPROVING BALL THROWING BASIC MOVEMENT COMPETENCY BY APPLYING THE GAME LEARNING MODEL IN THE IV GRADERS OF SD MUHAMMADIYAH 6 KAMPUNG SEWU OF JEBRES SUBDISTRICT OF SURAKARTA - Ngaliyah, Siti (Jurnal Phederal Penjas, 2012)
Siti NgaliyahPhysical Education, Health and Recreation Education Program, Teacher Training and EducationFaculty of Surakarta Sebelas Maret UniversityAbstract: The attempt of improving the ball throwing basic movement competency by applyingthe game learning model in the IV graders of SD Muhammadiyah 6 Kampung Sewu of JebresSubdistrict of Surakarta in the school year of 2011/2012. Thesis, Surakarta: Teacher Trainingand Education Faculty, Surakarta Sebelas Maret University, September 2012.The objective of research is to improve the ball throwing basic movement competency byapplying the game learning model in the IV graders of SD Muhammadiyah 6 Kampung Sewu ofJebres Subdistrict of Surakarta in the school year of 2011/2012.This research was a classroom action research. This study was conducted in two cycles, each ofwhich consisted of planning, acting, observing, and reflecting. The subject of research was theIV graders of SD Muhammadiyah 6 Kampung Sewu, Jebres Subdistrict, Surakarta in the schoolyear of 2011/2012 consisting of 21 students: 11 boys and 10 girls. The data source derived fromteacher and student. Technique of collecting data used was demonstration test, observation andcognitive test. The validity test was done using data triangulation conducted by collaborator,physical education and observer. Techniques of analyzing data used in this research were astatistical descriptive comparative and critical analyses.The result of research showed that the application of game learning model could improve ballthrowing basic movement competency from pre-cycle to cycle I, from cycle I to cycle II. Theresult of ball throwing basic movement competency in pre-cycle was 38.09%; it increased to61.9% in cycle I and to 80.95% in cycle II.From the result of research, it could be concluded that: (1) the application of game learningmodel conducted could improve the students? enthusiasm in learning the ball throwing basicmovement, (2) the application of game learning model conducted could improve the students?capturing power on the activity to be done, and (3) the application of game learning modelconducted could improve the ball throwing basic movement competency of the IV graders of SDMuhammadiyah 6 Kampung Sewu of Jebres Subdistrict of Surakarta in the school year of2011/2012.Keywords: ball throwing basic movement, game.